New, Not Different: Data-Driven Perspectives on Science Festival Audiences. Issue 2 (April 2019) - Nielsen, Katherine; Gathings, M. J.; Peterman, Karen
This commentary explores the kinds of audiences who attend science festivals in the United States by examining data from nearly 10, 000 attendees from 24 festivals. Findings are presented to describe festival audiences overall and in comparison to national census and polling data. Results are similar to those for other public science events, with the majority of attendees being well-educated and middle-class. Even so, approximately two thirds of festival-goers are new each year. The findings are discussed in relation to evidence that begins to establish a typology of public science event attendees, and the need to reach "new" versus "different" audiences.